A new chart of the vast Atlantic or Western Ocean, including the sea coast of Europe, Africa, America and the West India Islands: with the banks, shoals, rocks & course of sailing from one continent to the other laid down from the latest discoveries & regulated by numerous astronomical observations - Bowen, Thomas, d. 1790.;Bowles, Carington, 1724-1793. (Carington Bowles, 1762)
Map of trade routes across the Atlantic Ocean. Includes parts of North America, South America, Central America, Europe, and Africa as far south as the equator. Shows soundings off Newfoundland coast; relief shown pictorially. Countries, some islands, and major cities are labeled. Includes note about survey sources, latitude, and longitude in lower right corner. Prime meridian: London.